MASYARAKAT SAMIN DITINJAU DARI SEJARAH DAN NILAI-NILAI PENDIDIKAN KARAKTER - V. Indah Sri Pinasti; Puji Lestari (Universitas Negeri Yogyakarta, 2017)
ABSTRACTThis study aims to (1) to know factors are causing Samin communities remain at the values and traditions, (2) to determine the values and traditions of what is local wisdom Tribe Samin, and (3) to know the values and traditions Samin communities in terms of character education. In this research, the research team used ethnographic research methods. The ethnographic method is a method used to describe things that are associated with Samin community in more depth. The results showed that the teachings of Samin Samin triggered by Surosentiko in 1890 and readily accepted by society Blora. This is because the state of Blora society in the 19th century is very alarming. Besides the natural conditions that are less potentially, also pressure from the colonial government that is characterized by the influx of money economic system, as well as the demands of high taxes. Expropriation of land owned by the people who made teak forests belonging to the state and the influx of Western culture makes Samin communities chose to alienate her from the pressures of life are different from them. Keywords: Historicity, normativity, Samin community, Character Education